1002. Epidemiology of Pneumococcal Bacteremia in a Large Tertiary Center. (26th November 2018) - Asis, Aristotle; Gutierrez-Asis, Esmeralda; Hassoun, Ali
Abstract: Background: Streptococcus pneumoniae remains an important cause of bacteremia in the United States with high morbidity and mortality despite readily available treatment and vaccines. Increased incidence of bacteremia observed during 2017–2018 season. Methods: Retrospective chart review of patients admitted with pneumococcal bacteremia over the last two winter seasons. Demographics, laboratory data, ICU stay, need for ventilation or pressor, comorbidities, and mortality were collected. Results: Fifty-three patients enrolled. 62% admitted during 2017–2018. Sixty-six percent white, 60% male, mean BMI 27 (38% had normal BMI). Mean age was 55 years (1–93) (57% > 61). Mean hospital length of stay was 7.8 days (1–30). More than 40% required ICU stay. The use of NPPV, vasopressors, and mechanical ventilation were 6%, 15%, and 17%, respectively. Most common presentation: dyspnea 30% and fever 18%. Smoking history (55%). Eighty percent of these patients had pneumonia. Resistance to penicillin 9% and intermediate susceptibility 6%. Resistance to erythromycin 44% and trimethoprim-sulfamethoxazole 12% which increased during winter 2017 (52% and 12%) compared with winter 2016 (30% and 10%). Only 2% of patients with pneumonia had positive sputum culture for pneumococcus and 62% had positive serum pneumococcal antigen with bacteremia. Positive co-detection of bacterial or viral targets in sputum using Multiplex PCR did not correlate with mortality and hospital stay but they were more likely needed ICU stay, use of vasopressor and mechanical ventilation. 43% of empiric therapy was as recommended by IDSA guidelines. Comparing 2016 vs. 2017 seasons, mortality (15% vs. 6%), hospital stay (9 days vs. 7 days), use of NPPV (5% vs. 6%) mechanical ventilation (15% vs. 18%) and vasopressor (5% vs. 21%). No correlation between influenza infection and bacteremia. Overall 6-month mortality and re-admission rate was 9% and 2%, respectively. Mortality was higher in overweight patients (60% vs. 20%), non-smokers (40% vs. 20%), coronary artery disease (40%) and congestive heart failure (40%). Conclusion: Pneumococcal bacteremia cause significant morbidity and mortality, we observed less mortality and hospital stay, but more use of NPPV, mechanical ventilation, and vasopressor during 2017–2018 season which had widespread influenza like activity. Disclosures: All authors: No reported disclosures.